2016
DOI: 10.5334/sta.433
|View full text |Cite
|
Sign up to set email alerts
|

What Explains Criminal Violence in Mexico City? A Test of Two Theories of Crime

Abstract: There are competing theories of what drives crime in cities and neighbourhoods. Two widely cited theoretical approaches focused on social disorganization and institutional anomie propose different explanations for the causes and dynamics of criminality. Yet these theories are seldom empirically tested, much less acknowledged, outside of North America and Western Europe. This article considers their applicability in Mexico's capital, a sprawling metropolis of more than 20 million people. The authors administer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It is also necessary to weigh up the security of immigrants themselves, especially when they try to enter the host country illegally because of human trafficking networks (Czaika & de Haas, 2013), that have caused the loss of human lives, notably in routes from North Africa to Southern European countries and, more recently, related to the Syrian civil war (Ferreira, 2016a, pp. 1–2).…”
Section: Migration-security Nexusmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also necessary to weigh up the security of immigrants themselves, especially when they try to enter the host country illegally because of human trafficking networks (Czaika & de Haas, 2013), that have caused the loss of human lives, notably in routes from North Africa to Southern European countries and, more recently, related to the Syrian civil war (Ferreira, 2016a, pp. 1–2).…”
Section: Migration-security Nexusmentioning
confidence: 99%
“…91–93). Outside the EU, the Syrian conflict and political instability in MENA region do not seem to suggest a decrease in migration and refugee flows during the next years, which makes even more urgent to review the Dublin system (Ferreira, 2016a, p. 2). Restrictive policies will not stop irregular migration flows in the EU and will not increase internal security in ‘EU’rope (Völkel, 2017, p. 93).…”
Section: The Eu Vision: Between Fragmentation and Integrationmentioning
confidence: 99%
“…GWR becomes a valuable tool in identifying local areas within a city that may have varied social or economic environments that influence crime differently. Supporting this trend, Vilalta and Muggah (2016) used GWR to examine which theories of crime, social disorganization or institutional anomie, influenced Mexico City's crime environment. The authors observed local spatial variation with variables representing the two different theories and their relationships with crime throughout Mexico City.…”
Section: Local Spatial Variation In Crimementioning
confidence: 99%
“…The evaluation of the incidence of common jurisdiction crimes in the capital cities of Mexico is an essential activity in the planning of public security, not only because 17.9 percent of the total population of Mexico resides there, but also because they use a considerable amount of human, economic, and technical resources [7]. Moreover, public security and crime victimization have a direct impact on the quality of life of the population [8]- [10].…”
Section: Introductionmentioning
confidence: 99%